Implications of Congenital Blindness in Body Image: An Integrative Review - Morgado, Fabiane Frota da Rocha (2019)
This study aimed to investigate, through an integrative review, the main implications of congenital blindness on body image. An article search process, without publication date limit, with the descriptors “congenital blindness” and “congenitally blind”, in the Scopus, PsycINFO, Web of Science and PubMed databases was performed. Among the 3,612 publications found, 20 were analyzed. The implications of blindness were discussed in five distinct areas: eating disorders, self-representation, body dissatisfaction, body experience and neural representation of self-concept. It was concluded that it is essential to value a complex series of psychosocial factors in the development of people with congenital blindness, which could impact positively or negatively the body image formation.